Managing Scale Insects on Ornamental Plants - Eileen A. Buss; Adam Dale (EDIS, 2016)
Scale insects are a diverse group of piercing-sucking pests (Hemiptera) commonly found on ornamental plants in landscapes and nurseries. There are over 180 species of scale insects in Florida, but only a small percentage are important pests of ornamental plants. They damage plants and secrete a waxy covering that makes them difficult to control using most chemical control measures. This revised 6-page fact sheet differentiates between armored and soft-scale insect pests and lists common types of each, provides information about the biology of scale insects and how to identify them and the damage they cause, describes how to scout and monitor for scale insects, and lists several methods for prevention and control of scale insect invasions. Written by Eileen A. Buss and Adam Dale, and published by the Department of Entomology and Nematology, July 2016.